(untitled) (International Journal on Stereo & Immersive Media, 2025)
Practice-based creative research, also known as research-creation, exists in a tenuous position between art and academia. There has been significant, ongoing research into the role of curatorial processes, research, and public-facing events as forms of knowledge production which draw from both traditional informational methodologies and creative or artistic approaches. However, much extant work on this subject is centered on gallery and museum spaces. This paper describes a creative research project carried out by a team of graduate students at Concordia University, which aims to bring research-creation into direct, engaged conversation with more traditional forms of academic research through the research collective’s development of interdisciplinary symposia. We discuss the importance of taking a design approach, including documentation and iterative practices, in order to create an environment in which creative research and scholastic research are treated as equally important forms of knowledge production. Specifically, we detail how the idea of meaningful methods influenced our approach, and how designing for connection and embodied experience are essential to creating event spaces which facilitate interdisciplinary knowledge exchange.